The Concept of Human Freedom in the Qadariyah and Jabariyah Traditions: A Critical Review - Nola Najla Mutia Afifah; Steviani Viqi Hidayah; Tyas Sandrina; Syamsul Rijal; Yokha Latief Ramadhan (Lembaga Yasin AlSys, 2026)
Although debates on human freedom and divine destiny occupy a central position in Islamic theological discourse, the historical and socio-political roots of the Qadariyah–Jabariyah controversy require further critical examination. This study aims to analyze the historical development and theological debate between the Qadariyah and Jabariyah schools of thought concerning human agency, divine will, and moral responsibility. Employing a qualitative library research design with historical-critical and comparative approaches, this study examines classical primary texts and relevant contemporary secondary literature through textual hermeneutics and comparative thematic analysis. The findings indicate that the debate emerged from post-conflict political dynamics, particularly internal disputes and crises of leadership legitimacy, which generated polemics concerning the status of sinners, the meaning of faith, and the relationship between qada’ and qadar. The Qadariyah, represented by Ma’bad al-Juhani and Ghailan al-Dimashqi, emphasize human qudrah and individual moral responsibility, interpreting human freedom as the capacity to choose within the limits of Sunnatullah, especially through the distinction between musayyar and mukhayyar. Conversely, the Jabariyah, associated with Jahm ibn Safwan and its moderate variants, emphasize the dominance of divine will; while the extreme variant denies human volition, the moderate variant acknowledges kasb as the human acquisition of actions created by God. The analysis demonstrates that these epistemic differences are not merely doctrinal disputes but are also shaped by socio-political dynamics and intellectual interactions across traditions. This study concludes that a moderate understanding that integrates reason, human endeavor, and divine sovereignty provides a constructive foundation for contemporary ethics, education, and religious policy. By addressing manuscript limitations and historiographical bias, this study contributes to a more transparent and contextual understanding of classical Islamic theological debates.